Information Seeking Behaviour in Electronic Environment: A Study of Engineering College Users in West Bengal - Ghosh, Uttam Kumar; Rajawat, Kumkum (Journal of Advanced Research in Library and Information Science; Vol 8 No 2 (2021): Journal of Advanced Research in Library and Information Science, 2021)
This research is concerned with the “Information seeking behaviour in Electronic Environment: A Study of Engineering Colleges Users in West Bengal.” This analysis is based on the data composed through a questionnaire from Users of the Engineering College of West Bengal. This research deals with the analysis and interpretation of collected data by employing appropriate statistical tools and techniques wherever necessary. Data were composed by using a questionnaire from 3468 Respondents in Engineering Colleges of West Bengal. How to cite this article:  Rajawat K, Ghosh U. Information Seeking Behaviour in Electronic Environment: A Study of Engineering College Users in West Bengal. J Adv Res Qual Control Mgmt 2021; 8(2): 13-20.